2009
DOI: 10.1001/archgenpsychiatry.2008.524
|View full text |Cite
|
Sign up to set email alerts
|

Association of Variants in DISC1 With Psychosis-Related Traits in a Large Population Cohort

Abstract: Variants in DISC1 affect the level of social anhedonia, a cardinal symptom of schizophrenia in the general population. DISC1 might be more central to human psychological functioning than previously thought, as it seems to affect the degree to which people enjoy social interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 48 publications
(73 reference statements)
1
44
0
Order By: Relevance
“…Meanwhile, an association between the Disrupted In Schizophrenia gene and the social anhedonia trait, a cardinal symptom of schizophrenia spectrum disorder, has been reported [34]. Variants of the p250 guanosine triphosphatase-activating protein gene have been found to play a role in the negative schizotypy dimension and interpersonal schizotypy factors [15].…”
Section: Schizotypal Personality Disordermentioning
confidence: 99%
“…Meanwhile, an association between the Disrupted In Schizophrenia gene and the social anhedonia trait, a cardinal symptom of schizophrenia spectrum disorder, has been reported [34]. Variants of the p250 guanosine triphosphatase-activating protein gene have been found to play a role in the negative schizotypy dimension and interpersonal schizotypy factors [15].…”
Section: Schizotypal Personality Disordermentioning
confidence: 99%
“…16,26,[36][37][38] Association of DISC1 with psychosis-related traits has been reported in Finnish population. 39 A genome-wide association study has shown nominal association for SCZ with the SNPs near the DISC1 translocation break point. 40 These results support a role for TSNAX/DISC1 genetic variation in conferring susceptibility to both SCZ and BPAD.…”
Section: Introductionmentioning
confidence: 99%
“…These risk alleles have previously been associated with schizophrenia, bipolar disorder, and social and physical anhedonia, mainly in females. 1,7 Reports suggest that heritability of neuroticism, anxiety and depression is higher in females than in males, and that the genes involved differ between men and women. [8][9][10] We tested SNPs and models specifically chosen on the basis of earlier evidence, and hence do not believe that stringent multiple testing corrections are appropriate, but these results need to be replicated in other suitable cohorts before variation in DISC1 is fully accepted as contributing to normal variation in neuroticism and mood.…”
mentioning
confidence: 99%
“…The discovery of a novel FAD-dependent protein, renalase, was reported in 2005. 7 Renalase was identified using an in silico approach that aimed to discover novel proteins secreted by the kidney. The renalase protein sequence contains a highly conserved N-terminal FAD-binding domain and an amine oxidoreductase domain.…”
mentioning
confidence: 99%
See 1 more Smart Citation